Challenges, Strategic Partners and Scenarios for Colombian Foreign Policy during the Post-conflict era - Pastrana, Eduardo (2017)
This article addresses Colombian foreign policy in the context of the post-conflict period. First, it establishes the relationship between conflict and foreign policy during the governments of Andrés Pastrana (1998-2002) and Álvaro Uribe (2002-2010), and explains the turn that occurred with the arrival of Juan Manuel Santos to the presidency (2010- present), the peace talks with the Revolutionary Armed Forces of Colombia (FARC). Second, it analyzes the global scenarios in which Colombia wants to deploy a more active, propositive and autonomous new international image in a post-conflict context. Third, it identifies the extra-regional powers that are, or can be, strategic partners in the implementation of the peace agreements and the new international projection of the Colombian state. Fourth, it postulates which countries and regional institutions are fundamental for addressing some of the more complex post-conflict challenges. Fifth, it formulates Colombia’s main domestic challenges in the implementation of the agreements, both for the construction of a stable and lasting peace, and for the enhancement of its international projection.